2016
DOI: 10.3390/buildings6020014
|View full text |Cite
|
Sign up to set email alerts
|

Family Structures, Relationships, and Housing Recovery Decisions after Hurricane Sandy

Abstract: Abstract:Understanding of the recovery phase of a disaster cycle is still in its infancy. Recent major disasters such as Hurricane Sandy have revealed the inability of existing policies and planning to promptly restore infrastructure, residential properties, and commercial activities in affected communities. In this setting, a thorough grasp of housing recovery decisions can lead to effective post-disaster planning by policyholders and public officials. The objective of this research is to integrate vignette a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Studies have started to investigate the impact of family environments (e.g., support exchanges) on older adults' responses to disaster and related health consequences. These studies have shown the importance of family as the context for resilience, but few studies have examined the interconnected health consequences of family members (Cong, Liang, and Luo 2022;Cutter et al 2013;Kaniasty and Norris 1993;Kuntz 2015;Lindell 2013;Nejat, Cong, and Liang 2016). Guided by the principle of linked lives from the perspective of life course, which emphasizes the importance of the influence of others on an individual's behaviors and health outcomes, one focus of this study is on how family members' conditions affect an individual's health and mental health consequences (Elder and Johnson 2003).…”
Section: Family Contexts: Linked Livesmentioning
confidence: 99%
“…Studies have started to investigate the impact of family environments (e.g., support exchanges) on older adults' responses to disaster and related health consequences. These studies have shown the importance of family as the context for resilience, but few studies have examined the interconnected health consequences of family members (Cong, Liang, and Luo 2022;Cutter et al 2013;Kaniasty and Norris 1993;Kuntz 2015;Lindell 2013;Nejat, Cong, and Liang 2016). Guided by the principle of linked lives from the perspective of life course, which emphasizes the importance of the influence of others on an individual's behaviors and health outcomes, one focus of this study is on how family members' conditions affect an individual's health and mental health consequences (Elder and Johnson 2003).…”
Section: Family Contexts: Linked Livesmentioning
confidence: 99%
“…38 The problem of social vulnerability is a feature of both developing and developed countries in the aftermath of disaster, for example, survivors of hurricane Sandy who lived with family members before the disaster were less likely to relocate than those who lived alone, underscoring the vulnerability of the single individual in rebuilding and decision-making during the recovery. 5 Various studies in the past have established the role of household factors in disaster recovery, either individually or in combination with other factors such as external aid, government policies, and disaster management. 43,45,47 Household characteristics such as family size, the number of earning members, sources of income, literacy, and gender composition substantially impact the recovery process.…”
Section: Domain Descriptionsmentioning
confidence: 99%
“…3 However, the recovery process is the least understood aspect of disaster management. 4,5 It is a complex and multidimensional process involving the physical, social, economic, and institutional components of community life. 6 There is a lack of clarity in defining what constitutes successful recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A snowball sampling technique was utilized in distributing the survey questionnaire. This technique is a sampling approach that allows survey units to enhance their data [55][56][57]. This method, which is also referred to as chain-referral or link-tracing [58], is considered effective and economical [59].…”
Section: Stage 3: Samplingmentioning
confidence: 99%